Validity and reliability of the Indonesian version of the 9-item Inflammatory Bowel Disease Questionnaire (IBDQ-9) - Esa, Dekta Filantropi; Shatri, Hamzah; Rumende, Cleopas Martin; Susilo, Adityo; Maulahela, Hasan; Fauzi, Achmad; Simadibrata, Marcellus (Medical Journal of Indonesia, 2023)
BACKGROUND Decreasing the quality of life (QoL) of patients with inflammatory bowel disease (IBD) will increase morbidity and mortality. A valid and reliable instrument is needed to assess the QoL of patients with IBD. This study aimed to analyze the validity and reliability of the Indonesian version of the 9-item Inflammatory Bowel Disease Questionnaire (IBDQ-9). METHODS This cross-sectional study was conducted using the Indonesian version of the IBDQ-9 in adult patients with IBD at the Gastroenterology Outpatient Clinic, Cipto Mangunkusumo Hospital, Jakarta, in November 2022. Patients aged 18 to 59 years who had experienced IBD for at least 2 weeks and provided informed consents were included. The total score of the IBDQ-9 Indonesian version was compared with the 36-item Short-Form Health Survey (SF-36) using the Spearman's correlation test. Reliability tests were examined using Cronbach’s alpha and the intraclass correlation coefficient (ICC). RESULTS A total of 124 participants were included in this study. The Spearman's test showed a high and significant result for the IBDQ-9 Indonesian version and the SF-36 (r = 0.769 and p<0.001). Cronbach’s alpha and ICC coefficient were equal to 0.883. CONCLUSIONS This study provided evidence of the good validity and reliability of the IBDQ-9 Indonesian version for assessing the QoL of patients with IBD in Indonesia.